The flexibly grouped classroom : how to organize learning for equity and growth - Doubet, Kristina, 1969- (Alexandria, Virginia : ASCD, 2022)
"Learn how to make classroom grouping more intentional and more fluid in order to deliver targeted and equitable instruction, cultivate student interests, and strengthen the learning community"--
Introduction: How Traditional Models of Grouping Fall Short -- The Purpose of Flexible Grouping -- Planning for Flexible Grouping -- The Progression of Flexible Grouping -- Procedures for Flexible Grouping -- Troubleshooting Flexible Grouping -- Portraits of Flexible Grouping -- Conclusion: Embracing the Promise of Flexible Grouping.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 22, 2022).
eBooks on EBSCOhost
Keywords: Ability grouping in education; Team learning approach in education; Inclusive education; Mainstreaming, Education; Groupement par aptitudes (Éducation); Apprentissage -- Travail en équipe.; Intégration scolaire; Ability grouping in education; Inclusive education; Team learning approach in education; Electronic books